Performance of intermittently scanned continuous glucose monitoring systems in people with type 1 diabetes: A pooled analysis. Issue 3 (19th December 2021) - Moser, Othmar; Sternad, Christoph; Eckstein, Max L.; Szadkowska, Agnieszka; Michalak, Arkadiusz; Mader, Julia K.; Ziko, Haris; Elsayed, Hesham; Aberer, Felix; Sola‐Gazagnes, Agnes; Larger, Etienne; Fadini, Gian Poalo; et al.
Abstract: Aims: To conduct a pooled analysis to assess the performance of intermittently scanned continuous glucose monitoring (isCGM) in association with the rate of change in sensor glucose in a cohort of children, adolescents, and adults with type 1 diabetes. Material and Methods: In this pooled analysis, isCGM system accuracy was assessed depending on the rate of change in sensor glucose. Clinical studies that have been investigating isCGM accuracy against blood glucose, accompanied with collection time points were included in this analysis. isCGM performance was assessed by means of median absolute relative difference (MedARD), Parkes error grid (PEG) and Bland‐Altman plot analyses. Results: Twelve studies comprising 311 participants were included, with a total of 15 837 paired measurements. The overall MedARD (interquartile range) was 12.7% (5.9‐23.5) and MedARD differed significantly based on the rate of change in glucose ( P  < 0.001). An absolute difference of −22 mg/dL (−1.2 mmol/L) (95% limits of agreement [LoA] 60 mg/dL (3.3 mmol/L), −103 mg/dL (−5.7 mmol/L)) was found when glucose was rapidly increasing (isCGM glucose minus reference blood glucose), while a −32 mg/dL (1.8 mmol/L) (95% LoA 116 mg/dL (6.4 mmol/L), −51 mg/dL (−2.8 mmol/L)) absolute difference was observed in periods of rapidly decreasing glucose. Conclusions: The performance of isCGM was good when compared to reference blood glucose measurements. The rate of change in glucose for both increasing and decreasing glucose levels diminished isCGM performance, showing lower accuracy during high rates of glucose change.